The improvement of mathematics understanding ability on system of linear equation materials and students learning motivation using geogebra-based educational games - Septian, Ari; Monariska, Erma (Universitas Islam Raden Intan Lampung, INDONESIA, 2021)
The purpose of this research is to determine the improvement of students' mathematical understanding ability on a system of linear equations using GeoGebra-based game education. This research use quasi-experimental that was conducted on two classes of the school in Indonesia. Class X MIPA 4 as experimental class and X MIPA 3 as control class. Based on the results the average score of N-Gain value analysis, mathematical concept understanding ability in the experimental class is 0.55, and the control class average score is 0.30. Based on the calculation, the Asymp. Sig. (2 tailed) of 0.000 is obtained. Because the significance score is obtained less than 0.05, thus it is rejected and is accepted. So, it can be concluded that the improvement of students' mathematical understanding ability using GeoGebra-based game education is better than the improvement through ordinary learning. The learning motivation of students using GeoGebra-based game education as a positive learning media, but there is no relationship between learning motivation and students' mathematical understanding using GeoGebra-Based Game Education.